Methodological issues study sexuality of persons with autism spectrum disorders - M. Dubovik (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article touches upon some methodological problems concerning the exploration of sexuality of individuals with autism spectrum disorder. The author focuses on three groups of such problems, proposing the possible ways of solving them. The foreign researchers’ experience in such methodological issues is alsoanalyzed in the article. The author describes the possibilities of nomothetic and idiographic approaches in the study of sexuality of individuals with ASD. Psychological testing is supposed to be the method which contains the advantages of both approaches. The article makes an observation of the problems that arise at the stage of forming samples with autistic individuals. The problem of primary diagnosis of autism is considered to be crucial for solving this group of methodological difficulties. Special focus is made on the triad of qualitative impairments in autism. The author shows how the deficits in social, communication and imagination spheres cause another methodological problem in choosing research methods in the study of sexuality of individuals with ASD. In general, the article shows the opportunities of parental perspective as a method of collecting data in the researches on sexuality of individuals with ASD. Since this method makes it possible to assess such phenomena, taking into account the methodological problems described in the article.